(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition affecting social interaction, communication, and behavior. Given the increasing prevalence and significant impact on child development, this study examines how physical activity can aid in the development of children with ASD. The main objective is to investigate the specific benefits of physical activity, identify effective activities for this group, and discuss their integration into the daily lives of children with ASD. Using a quali-quantitative approach and a systematic literature review, recent studies on physical activity interventions applied to children with ASD were analyzed. Inclusion criteria involved articles published in the last five years in English, focused on interventions such as postural control, adapted physical education, sleep regulation, and parent-mediated programs. The electronic search was conducted in databases such as MEDLINE/PubMed, Science Direct, and SciELO, using descriptors like <autism>, <Autism disorder>, and <physical activity>. Out of the 1636 studies initially identified, 586 were deemed relevant after screening, and four met the final criteria. The results indicate that regular physical activity brings multiple benefits to children with ASD, such as improvements in motor skills, reduction in anxiety, and enhancement of sleep quality. Structured exercise programs, including traditional exercises and exergames, were found to be effective in developing motor skills and executive functions in these children. Parent-mediated interventions were also beneficial, highlighting the importance of family involvement. We conclude that physical activity is a valuable and low-risk intervention that significantly contributes to the development of children with ASD. However, effective implementation requires proper planning and specialized professional support. There is still a need for more detailed clinical studies to validate these interventions in the long term. Therefore, promoting professional training and family engagement is essential to maximize the benefits of physical activity in autistic children.